What is the link between renewable&non-renewable energy, foreign direct investment, economic growth, and ICT on Ecological Footprint? Evidence of Environmental Kuznets Curve from European Union Countries and Turkey - Demir, Fatih; Bölük, Gülden (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
The purpose of this paper is to investigate the role of FDI, ICT, fossil, and renewable energy consumption on EFP in 25 EU countries and Turkey. In this context, we set up panel threshold models by using data over the 1990-2014 period to test environmental Kuznets curve (EKC) and Pollution Haven Hypothesis (PHH) in these countries. Contrary to previous EKC studies in the literature, the current study employs the more comprehensive indicator of environmental quality than emissions (namely, ecological Footprint, EFP) and examines the role of FDI and ICT on EFP for the first time in the EU countries and Turkey. Moreover, we analyzed the threshold effects of ICT and FDI on other variables. Our results found evidence supporting the EKC and PHH hypothesis when the ICT has been used as a threshold variable. Moreover, our study reveals that while FDI inflow and fossil energy worsen the environmental deterioration, ICT and renewable energy positively affect the environmental quality in EU and Turkey. Policy implications have been presented in the conclusion part.